Herencia de la resistencia al complejo Cercospora spp. en líneas de maíz tropical - Narro L. Luis (Acta Agronómica, 2005)
Se evaluó un diseño dialélico (Griffing Modelo 1) entre 10 líneas endogámicas de maíz tropical contrastantes en su reacción a Cercospora spp. (5 tolerantes y 5 susceptibles), en tres localidades en lotes bajo siembra directa, con presencia natural del patógeno e inoculación artificial, para la variable índice de enfermedad (escala 1 a 5). En el análisis de varianza, por localidad y combinado, los efectos de habilidad combinatoria general (hcg), habilidad combinatoria específica (hce), y recíprocos resultaron altamente significativos; siendo >10 veces mayor los efectos de la hcg que los de hce, indicando predominio de la acción genética aditiva. Resultados también sugieren que la resistencia está controlada por efectos maternos o de citoplasma. La acumulación de genes de resistencia y la conformación de variedades sintéticas tolerantes es una alternativa a implementar en programas del mejoramiento de resistencia a Cercospora de maíces tropicales.

ABSTRACT

Inheritance of resistance to Cercospora Complex in tropical maize (zea mays) inbred lines. Inheritance of resistance to the maize disease complex caused by Cercospora spp on tropical maize was studied by generating and evaluating a diallel mating model (Griffing model I) using ten corn inbred lines with contrasting levels of disease reaction (5 tolerant and 5 susceptible). Parental lines and their crosses, both direct and reciprocal, were evaluated in three locations using conservation tillage and inoculated artificially with inoculum prepared using a mixture of foliar maize diseases collected from several farmer’s fields. Analysis of variance for the variable index of disease (scale 1 to 5), both locality and combined, the general combining ability (hcg), specific combining ability (hce), and reciprocal effects were highly significant, with the hcg portion being >10 times greater than the hce component, indicating that the genetic action is predominantly additive. Data collected suggested that maternal or cytoplasmic effects are important in controlling disease resistance. Accumulation of resistance genes through the development of synthetic varieties is an alternative to be implemented in maize breeding programs workin towards the development of gray leaf spot resistant tropical maize germplasm.

Key words: Zea mays, Cercospora zeae maydis, gray leaf spot of maize, diallel mating, general combining ability, specific combining ability, reciprocal effects.